Mahkamah Konstitusi dan Penafsiran Hukum yang Progresif - Mahrus Ali (Jurnal Konstitusi, 2016)
The main maxim of progressive law is law for human, not human for law. Since stressing to human existence to enforce the law, the progressive law rejects the status quo based on legal positivism, the existence of written legal text containing many weaknesses, and pays more attentions to the role of human behavior. In the context of constitutional court roles as the sole and the highest interpreter of the constitution, the interpretation of progressive law wants the institutional court not strictly rely on the written text, not to use legal positivism as a paradigm in interpreting the law, but focusing on rechtsidee, values, and way of life written on Pancasila to implement the substantive justice, not the existence of legal texts in constitution of  1945.